2008
DOI: 10.7202/018776ar
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Removal of Metal Ions from Effluents Using Seaweeds, Alginate Derivatives and Other Sorbents

Abstract: AbstractBiosorbents, especially those derived from seaweed (macroscopic algae) and alginate derivatives, exhibit high affinity for many metal ions. Because biosorbents are widely abundant (usually biodegradable) and less expensive than industrial synthetic adsorbents, they hold great potential for the removal of toxic metals from industrial effluents. Various studies have demonstrated the efficiency of living and non-living micro-organisms, such as bacteria, yeasts, moulds, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 225 publications
0
6
0
Order By: Relevance
“…Oscillatoria spp., Calothrix spp. and Synechoccus spp., yet the beneficial application of cyanobacteria in remediation of contaminated natural aquatic environments or industrial effluents has still not been optimally defined (Fiset et al 2008). Deng et al (2007) observed that the green marine algae Cladophora fascicularis can be used as an efficient biosorbent material for removal of Pb(II) from wastewater (as a function of time, initial pH, initial Pb(II) concentrations, temperature and co-existing ions).…”
Section: Cyanoremediationmentioning
confidence: 99%
See 2 more Smart Citations
“…Oscillatoria spp., Calothrix spp. and Synechoccus spp., yet the beneficial application of cyanobacteria in remediation of contaminated natural aquatic environments or industrial effluents has still not been optimally defined (Fiset et al 2008). Deng et al (2007) observed that the green marine algae Cladophora fascicularis can be used as an efficient biosorbent material for removal of Pb(II) from wastewater (as a function of time, initial pH, initial Pb(II) concentrations, temperature and co-existing ions).…”
Section: Cyanoremediationmentioning
confidence: 99%
“…The robust ability of the blue algae for As accumulation can serve as cyanoremediation to efficiently remove arsenic from aquatic environments. Although the role of cyanobacteria has been established for remediation of aquatic and wetland ecosystems (Fiset et al 2008) and of agricultural rice fields (Tripathi et al 2008) for metals recovery through seaweeds including Anabaena spp., Nostoc spp. Oscillatoria spp., Calothrix spp.…”
Section: Cyanoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order for alginate to be able to be used in the biomedical and pharmaceutical field, it must be safe for the body and biocompatible, that is, it must have high purity. A crude alginate purified by a multistage extraction method is devoid of or contains impurities in a low amount and can be taken orally without causing a response from the immune system [ 2 , 3 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal ions such as Pb 2+ , Cd 2+ , Cu 2+ , and Zn 2+ can be removed by alginate hydrogels, according to the research. 13,18 Moreover, the blending or modification of sodium alginate with nanomaterial can increase the adsorption sites for heavy metals, thus the adsorption capacities can be improved. Carbon nanotubes (CNTs) have drawn high attention in heavy metal ions detection due to their unique chemical and physical properties such as high surface area, electric conductivity, and excellent mechanical flexibility.…”
mentioning
confidence: 99%